Penegakan Hukum Pidana Terhadap Kekerasan Berbasis Gender Online - Ismail, Nurul Hadija; Sopacua, Margie Gladies; Muammar, Muammar (PATTIMURA Law Study Review, 2025)
KBGO as internet-facilitated violence is almost the same as KBGO in the real world. KBGO occurs as a result of the development of widespread internet coverage, sophisticated distribution of information technology, and the popularity of social media. The National Commission on Violence Against Women classifies several types of KBGO, namely approaches to deceive (cyber grooming), online harassment (cyber harassment), hacking, illegal content (illegal content), invasion of privacy (infringement of privacy), threats to distribute personal photos/videos (malicious distribution), defamation (online defamation), and online recruitment (online recruitment). According to Article 1 number 3 of Law Number 11 of 2008 concerning Information and Electronic Transactions (hereinafter abbreviated as the ITE Law), it is a technique for collecting, preparing, storing, processing, announcing, analyzing, and/or disseminating information. One of the information technology products that has an important role and has succeeded in spurring changes in the social order is the internet. The internet not only spurs aspects that have a positive impact, but can also have a negative impact, one of which is crime in the realm of the internet (cyber crime). This research writing uses a normative legal research type, with descriptive analysis research specifications. The data used are secondary data obtained through literature studies, then qualitative analysis is carried out. The results of this study indicate that the legal regulation of online gender-based violence in legislation as a whole, there are several legal instruments that can be used to ensnare perpetrators of online gender-based violence in Indonesia, but there is still a lack of regulations that specifically deal with gender-based violence in cyberspace. Existing laws are still general and do not provide specific protection against the gender dimension in digital violence. Criminal law enforcement against online gender-based violence currently, for many victims who still feel that justice has not been fully achieved due to the slow legal process, social stigma, and lack of adequate support, limited knowledge of the community and law enforcement officers and the difficulty of deleting content that has been distributed.